Enhancing Happiness through Mindfulness, Gratitude, and Journaling: Insights from a Student Study - Shuchi Tiwari; Jyotsna Cherukuri (Digital Crossroads: Integrating Humanities, Science and Technology Edition 1, 2025)
This study investigates the impact of daily activities, relationships, mindfulness, gratitude, and journaling practices on happiness and overall well-being, proposing key influences in each area. We focus on four main hypotheses: Hypothesis 1 posit that daily activities and relationships significantly affect happiness ratings; Hypothesis 2 suggests that mindfulness practices enhance mental well-being; Hypothesis 3 indicates a correlation between gratitude practice and improved mood and overall well-being; and Hypothesis 4 anticipates that journaling positively contributes to nurturing happiness. This manuscript explores how targeted practices impact personal well-being. This manuscript examines the roles of dopamine, oxytocin, serotonin, and endorphins, evaluating their correlation with self-reported happiness, relationship satisfaction, and mindfulness outcomes. The study evaluates practices such as gratitude journaling, mindfulness exercises, and effective time management strategies to gauge their influence on students’ focus, mood, and life satisfaction. Additionally, we examine the relationship quality’s effect on happiness and whether mindfulness fosters mental resilience and relaxation. A structured course called "Happiness & Well-Being (22MN6HS103)" at VNR Vignana Jyothi Institute of Engineering and Technology, Hyderabad, with 153 students did the study to find out how certain practices affect student’s mental and physical health. Key findings reveal that gratitude journaling, mindfulness exercises, and effective time management strategies significantly influence students’ focus, mood, and life satisfaction. Additionally, relationship quality plays a vital role in happiness, while mindfulness fosters mental resilience and relaxation. Biological factors, including dopamine, oxytocin, serotonin, and endorphins, were examined to understand their correlation with self-reported happiness, relationship satisfaction, and mindfulness outcomes. The study’s significance extends beyond the academic setting, offering broader implications for educational policy, mental health strategies, and future research on integrating structured well-being practices into daily routines. It highlights the transformative potential of targeted interventions to enhance students’ happiness and overall well-being, paving the way for a more holistic approach to education and mental health.